Harry Potter and the deathly hallows - Rowling, J.K. (London : Bloomsbury, 2007)
Burdened with the dark, dangerous, and seemingly impossible task of locating and destroying Voldermort's remaining Horcruxes, Harry, feeling alone and uncertain about his future, struggles to find the inner strength he needs to follow the path set out before him.
Keywords: Potter, Harry (Fictional character -- Juvenile fiction; Good and evil -- Fiction; Hogwarts School of Witchcraft and Wizardry(Imaginary place) -- Juvenile fiction; Wizards -- Juvenile Fiction; England -- Fiction